Intertextual Echoes or Cultural Universals? Reassessing the Influence of Ancient Greek Poetry in The Mighty Thor series (issues 363–6) - Zbądzki, Jakub (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2024)
The purpose of this article is to reexamine the interpretation of comics 363–6 in Marvel’s The Mighty Thor series as a retelling of the Hellenistic mock epic poem Batrachomyomachia, a view expressed by scholars such as Nicholas Newman in his paper entitled The War of Frogs and Rats. The Batrachomyomachia in Marvel’s The Mighty Thor. The article proposes an alternative approach to reading these comics outside of the antique context, interpreting the similarities between the two works through the lens of cultural universals theory.